(untitled) (University of Khartoum Engineering Journal, 2022)
The modern communications is one of the most critical elements of modern cultures depicted in the 21th century. All of the recent civilizations depend on electronics and communication. Mobile wireless communication system is identified by ability to transfer information without using any current carrying conductor. The wireless fidelity WI-FI is the first step towards the adoption of IEEE802.11 standards which include the “IEEE 802ac” and “IEEE 802.11ad” sets. There standards permits wireless throughput rates in the gigabit levels. In this paper, a discussion of these standards will be detailed